Technologically innovative teaching and learning strategies in contexts of crises: lessons from COVID-19 in selected primary schools in Masvingo District, Zimbabwe - Magwa, Logic; Mayisela, Simangele; Chibidi, Inos (Frontiers in Education, 2025)
Many developing countries, especially in Africa, depended on the traditional form of teaching and learning, which was reconfigured due to the restrictions that came with the management of the COVID-19 pandemic. In view of this, this study sought to explore technologically innovative teaching and learning strategies that can be employed by teachers in Zimbabwe to ensure that teaching and learning processes persist despite constraining circumstances, such as pandemics. A qualitative and instrumental case study design with in-depth interviews and focus group discussions was employed. The independence and autonomy theory was used to provide a grounding base for understanding effective technologies that can be used in the context of crises. The study sample of 12 general teachers, two information and communication technology teachers, two educational psychologists, and 24 learners was drawn from the target population through a purposive sampling process. It was revealed that the adoption of e-learning, the use of mobile learning, the use of social media, and the use of virtual classrooms could allow teaching and learning processes to continue in the context of crises. The study recommends that learning institutions should formalise the use of various electronic platforms in education. The research also recommends the adoption, control, and management of various platforms, such as e-learning, mobile learning, social media use, and the use of virtual classrooms in the teaching and learning process.